Karakteristik Kimia Snack Bar Berbasis Tepung Ubi Jalar Ungu (Ipomea batatas), Tepung Kulit Buah Naga Merah (Hylocereus polyrhizus), dan Kacang Almond (Prunus dulcis) - Almira Fadila Sarasvati; Sukardi Sukardi; Sri Winarsih (Jurnal Riset, Inovasi, Teknologi & Terapan, 2026)
A snack bar is a commercial ready-to-eat food product that has a balanced nutritional quality that is useful for the body, including protein, carbohydrates, vitamins, and minerals. Snack bars are usually made from a mixture of wheat flour and soybean. To increase the fiber and antioxidant content of the snack bar, purple sweet potato flour is formulated with dragon fruit peel flour. The research method was factorial randomized complete block design (RCBD), with factor I: ratio of purple sweet potatoes to dragon fruit peel (100:0, 90:10, 80:20, 70:30%, factor II: concentration of almond nut (10% and 15%). The result showed that the ratio of 70% : 30% and 15% almond nut (T4G2) was recommended for product formulation based on the effectivity value by de Garmo analysis. It contains moisture of 13.31%, ash of 2.84%, protein of 10.22%, fat of 20.0%, fiber of 3.72%, and carbohydrate of 48.90%. Purple sweet potato flour and red dragon fruit peel flour have the potential to be used as snack bar raw materials, and their protein content can be increased by adding almonds.